Multiracial college students' experiences with multiracial microaggressions. Issue 4 (4th July 2017) - Harris, Jessica C.
Abstract: While research on monoracial college students' experiences with racial microaggressions increases, minimal, if any, research focuses on multiracial college students' experiences with racial microaggressions. This manuscript addresses the gap in the literature by focusing on multiracial college students' experiences with multiracial microaggressions, a type of racial microaggression. Utilizing qualitative data, this study explored 3 different multiracial microaggressions that 10 multiracial women experienced at a historically white institution including, Denial of a Multiracial Reality, Assumption of a Monoracial Identity, and Not (Monoracial)Enough to 'Fit In.'